Interactions between new and pre-existing dynamics in bimanual movement control - Serrien, Deborah J. (Springer, 2009)
Motor skills are commonly acquired through practice. This process not only involves acquisition of the particular task demands but also requires overcoming pre-existing modes. In the present study, interactions between new and intrinsic dynamics were evaluated. Accordingly, bimanual finger tapping with a 2:1 ratio was performed according to two training schedules: continuous (consecutive trials) and interrupted (non-consecutive trials with intermediate 1:1 in-phase performances). In addition, in-phase and anti-phase were probed before and after training. Behavioural output was assessed by means of temporal accuracy and variability, whereas neural activation patterns were determined by EEG coherence. Results showed that continuous practice resulted in improved performance with reduced coherence across the motor network. For interrupted practice, behavioural execution ameliorated, although it was inferior to performance with continuous practice. In terms of neural changes, the degree of intrahemispheric and midline connectivity did not reduce with interrupted practice, whereas interhemispheric connectivity increased. This signifies that short-term motor consolidation of the 2:1 task was disrupted due to intermediate performance of the in-phase mode. Furthermore, the probed in-phase and anti-phase pattern showed no behavioural changes, although neural alterations occurred that depended on training schedule and coordination mode. Overall, the observations illustrate bidirectional interactions between new and inherent dynamics during motor acquisition, raising issues about effective methods for learning skills and scheduling of practices in neurorehabilitation.